A Holistic Approach to Model the Kinetics of Photocatalytic Reactions - Bloh, Jonathan Z. (Frontiers in Chemistry, 2019)
Understanding and modeling the kinetics is an essential part of optimization and implementation of chemical reactions. In the case of photocatalytic reactions this is mostly done one-dimensionally, i.e. only considering the effect of one parameter at the same time. However, as shown herein, many of the relevant reaction parameters have mutual interdependencies that call for a holistic multi-dimentional approach to accurately model and understand their influence. Such an approach is described herein, and all the relevant equations given so researchers can readily implement it to analyse and model their reactions.